2010
DOI: 10.1002/hipo.20920
|View full text |Cite
|
Sign up to set email alerts
|

Trauma‐induced alterations in cognition and Arc expression are reduced by previous exposure to 56Fe irradiation

Abstract: Exposure to ionizing irradiation may affect brain functions directly, but may also change tissue sensitivity to a secondary insult such as trauma, stroke or degenerative disease. To determine if a low dose of particulate irradiation sensitizes the brain to a subsequent injury, C56BL6 mice were exposed to brain only irradiation with 0.5 Gy of 56Fe ions. Two months later, unilateral traumatic brain injury was induced using a controlled cortical impact system. Three weeks after trauma animals received multiple Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 61 publications
5
62
0
Order By: Relevance
“…Previous reports showed that miR21 levels in the hippocampus and cerebral cortex was up-regulated in TBI rodent, which suggested that the elevated miR21 might be involved in the intricate process of TBI course (Redell et al 2011;Rosi et al 2012). Additionally, others demonstrated that transgenic overexpression of miR21 in mice attenuated the beneficial hypertrophic response to spinal cord injury (SCI), whereas inhibition of miR21 augmented the astrocytic response after SCI (Bhalala et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that miR21 levels in the hippocampus and cerebral cortex was up-regulated in TBI rodent, which suggested that the elevated miR21 might be involved in the intricate process of TBI course (Redell et al 2011;Rosi et al 2012). Additionally, others demonstrated that transgenic overexpression of miR21 in mice attenuated the beneficial hypertrophic response to spinal cord injury (SCI), whereas inhibition of miR21 augmented the astrocytic response after SCI (Bhalala et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A mouse model of TBI was developed using a device that produces controlled cortical impact (CCI), permitting independent manipulation of tissue deformation and impact velocity. The left parietotemporal cortex was subjected to CCI [2 mm tissue deformation and 6.0 m/s (moderate)] or sham surgery (Rosi et al 2012). After injury, the incision was closed with interrupted 6-0 silk sutures, anesthesia was terminated, and the animal was placed into a heated cage to maintain normal core temperature for 45-min post-injury.…”
Section: Tbi Operationmentioning
confidence: 99%
“…All mice, regardless of injury type, were subjected to this surgical procedure. Mice that were randomly selected for the trauma only group (no irradiation) or the RCI treatment group were subjected to a controlled cortical impact (10, 11). The lesion was produced with a pneumatic impact device using a 3 mm diameter convex tip, mounted 20° from the vertical to account for the curvature of the mouse skull.…”
Section: Methodsmentioning
confidence: 99%
“…The behaviorally-induced immediate early gene Arc was investigated by Rosi et al (2008Rosi et al ( , 2010 and Raber et al (2013) for its expression in the dentate gyrus of mice. Both messenger RNA and protein levels in neurons showed behaviorally-induced upregulation which was inhibited by exposure to X-rays and low doses of 56 Fe ions.…”
Section: H Molecular Marker Changesmentioning
confidence: 99%